Faktor -Faktor Tekanan Kerja Yang Mempengaruhi Keseimbangan Kehidupan Kerja Dalam Kalangan Jururawat - Aisha, Nur Fadzlin; Ruslan, Rumaizah (Research in Management of Technology and Business, 2020)
Work stress is a psychosocial hazard and it has becoming a current global phenomenon. This study was conducted to identify the factors of work stress and to determine the relationship between work stress factors on work life balance among hospitals’ nurses around Johor. This study used quantitative method using questionnaire where an online survey through Google Form was employed. There were 80 complete forms returned and analysed by using the IBM Statistical Package for The Social Science (SPSS) version 25.0 software. The results showed that there was a significant correlation between the factors of work stress on work life balance among nurses. The interpersonal relationship factor in the workplace is the highest factor contributing to the work stress among nurses (r= 0.409, p